The EFL students’ online reading determinants: Perceiving from their selected folklore readings - Sumekto, Didik Rinan; Taufiqulloh, Taufiqulloh; Aryani, Made Ratna Dian (Indonesian Journal of Applied Linguistics, 2022)
In an attempt to increase reading performance at university level. This study aims at perceiving the experiential determinants of EFL students’ online reading performance. Data were collected from 182 undergraduate students’ self-rated questionnaire based on the assigned Indonesian folklores in English version through the online reading platforms. Data analysis used descriptive statistics and factor analysis. The results showed that EFL students’ reading habits and reading frequencies and trends were very supportive, whilst reading effectiveness and reading for pleasure supported their reading performance. Tests of chi-square’s four variables were statistically significant indicating the proportional majority of online reading activity. Meanwhile, the Principal Components Analysis (PCA) indicated two components and variables under the eigenvalues’ square root. The interpretation of two components was coherent with the pilot results on the online reading readability scale, analyzed the use of positive and negative affect items as undertaken from the pattern and structure matrix for PCA with the Obliging rotation. EFL students’ online reading is engaging accordingly since students accomplished their reading performance based on individual accessibilities and habits to understand the contents of genres. This study concludes that EFL students’ online reading performance has been practically facilitated by the technology devices multiply. Hence, four online reading variables increased EFL students’ reading awareness and performance accordingly.